A Note on Three Hellenistic Coins from the Collections of Russian Museums - SMIRNOV, Svyatoslav (Historia i Świat, 2018)
This study deals with three rare Hellenistic coins kept by two Russian museums: the State Historical Museum and the State Museum of Oriental Art. All specimens are of a great numismatic interest, firstly, because they belong to rare or previously unknown issues.